Identification of Self-Concept among Cancer’s Farmer Patients Undergoing Chemotherapy: A Descriptive Study - Septiani Wahdaniyah, Mellinia; Asmaningrum, Nurfika; Endrian Kurniawan, Dicky (Nursing and Health Sciences Journal (NHSJ), 2023)
Occupation in the agriculture sector is one of the contributors to health problems, one of which is cancer. The general treatment that can be given to cancer patients is chemotherapy. However, the side effects of chemotherapy can interfere with daily activities and cause feelings of helplessness. This condition influences changes in the self-concept of farmers. The purpose of this study is to identify the self-concept of farmers undergoing chemotherapy at Level III Baladhika Husada Hospital, Jember Regency. This study used a descriptive quantitative design. The sampling technique used purposive sampling with a total of 58 respondents. The data collection was conducted using a self-concept questionnaire. The data analysis technique used univariate analysis. The results of this study indicate that more than half of the farmers had a negative self-concept as many as 31 people (53.4%). Based on the evaluation of indicators, 31 people (53.4%) showed weak self-identity, 34 people (58.6%) had negative body image, 37 people (63.8%) had negative self-ideals, 33 people had low self-esteem (56.9%), and the disturbed role of 33 people (56.9%). The majority of farmers had a negative self-concept, which can be caused by several factors, such as changes in body condition, roles in the family, and changes in social relations. This study can be a basis for nurses to improve nursing practice by providing support and motivation to patients undergoing chemotherapy during the treatment process.